A high‐throughput method using Ultra‐Performance Liquid Chromatography to determine water‐soluble carbohydrate concentrations in pasture plants. (30th August 2017) - Maharjan, P.; Jacobs, J. L.; Deighton, M. H.; Panozzo, J. F.
Abstract: The determination of water‐soluble carbohydrate (WSC) concentrations in forages is important for quantifying forage feed quality as WSC is not only a major source of energy but is also associated with the grazing preferences of forages and subsequent intake by livestock. This study describes a high‐throughput ultra‐performance liquid chromatography (UPLC) method to analyse WSC concentrations of various forage samples. The application of the new method is demonstrated by investigating the WSC concentrations in (i) temperate forages at different tiller heights, and (ii) summer forage crops grown under rain‐fed and irrigated conditions. The UPLC method provided a more descriptive, specific and precise analysis of WSC concentration compared to the colorimetric method. Grass tiller height had a significant effect on total WSC concentration and individual sugar. With increasing tiller height, sucrose concentration increased and fructan and total WSC concentrations decreased. While irrigation treatment increased the dry‐matter yield of all nine summer forage crops analysed, there was no consistent effect of irrigation on WSC concentration.